Me-time is time for Allah - Seise, Claudia (Azizah) (AboutIslam, 2018)
We often feel overwhelmed by all the tasks we face in our everyday life; whether as employees, mothers, fathers, homemakers. We often wish for some time for ourselves, time to relax, time off. Some me-time.